INTERFERENSI BAHASA BUGIS DALAM PENGGUNAAN BAHASA INDONESIA LISAN MAHASISWA JURUSA PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNISMUH MAKASSAR - Muhammad Akhir; Supriadi Supriadi (JURNAL KONFIKS, 2017)
This study aims to describe the forms of syntactic interference in the use of Indonesian spoken Indonesian Student Department of Language Education and Literature Indonesia, FKIP Unismuh Makassar. The data in this study were obtained from oral speech that meet the criteria: (1) native speakers of Bugis language, (2) have studied Bugis language, (3) being open, friendly, and not easily offended. The data in this study were collected through observation, interview, and elicitation techniques. Further analyzed by using contrastive analysis to find forms of syntactic interference then incorporated into syntactic patterns. From the results of this research data analysis obtained some form of Bugis language syntax interference in the use of Indonesian language oral Indonesian Department of Education and Literature FKIP Unismuh Makassar which includes: (1) subject dating, (2) word order, (3) use of pronouns (4) the use of the same agentive particles to replace the agentive particles by, (5) the use of the same particles to represent to, (6) the use of the same particles to represent with, (7) the use of the proposition particles in to replace the prepositioned particles to. (8) the use of preposition particles in to express the preposition particles in, (9) the use of preposition particles in to express the preposition particles of (10) the date of the particle in to time, (11) the use of the new word as the sentence word, the preposition dating by in passive mandatory sentence, (13) denial at the beginning of the sentence. (14) the use of pronouns.